PENERAPAN SISTIM PENDUKUNG KEPUTUSAN DALAM SISTEM PENGUJIAN COMPUTERIZED ADAPTIVE TESTING - Rukli Rukli; Sri Hartati (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2011)
This study aims to make design decision support system adaptive to examinee ability to go to college.Decision support systems are made using one parameter logistic model by taking into account the difficulty level of questions adapted to the ability of the examinee. Questions are selected so that the items follow the ability of examinee more accurate assessment of ability with a lesser number of items.CAT a web-based applications require lesser number of items in determining the ability of examinee. College can determine the appropriate characteristics of the ability of examinee acceptance criteria for each department with domain weighting, and then determine the minimum level of capability that will be received and an appropriate amount to be received. Key word: Decision Support System, Computerized Adaptive Testing